2009
DOI: 10.3892/mmr_00000096
|View full text |Cite
|
Sign up to set email alerts
|

Common variants of the TLR9 gene influence the clinical course of HBV infection

Abstract: Abstract. Hepatitis B virus (HBV) infection leads to the development of liver inflammation, causing morbidity and mortality. Multiple factors influence HBV progression, including genetic factors. Toll-like receptor (TLR)9 plays a key role in innate immunity, and mutations in the genes encoding this receptor have been associated with liver damage progression. Our study aimed to investigate one-tag single nucleotide polymorphisms (rs187084) representing the majority of common variations in TLR9 in a population-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Although TLR stimulation shows antiviral effects in HCV-infection, TLR9 has only been demonstrated to bind to DNA virus, and the binding of HCV to TLR9 is unlikely 31. Numerous studies have investigated the effect of TLR9 (rs187084) on diseases, such as rheumatoid arthritis,34 HBV,35 and so on. However, most studies failed to show any significant associations, except in cervical cancer; one previous study found that rs187084 (T-1486C) affected susceptibility to cervical cancer in Chinese women 36.…”
Section: Discussionmentioning
confidence: 99%
“…Although TLR stimulation shows antiviral effects in HCV-infection, TLR9 has only been demonstrated to bind to DNA virus, and the binding of HCV to TLR9 is unlikely 31. Numerous studies have investigated the effect of TLR9 (rs187084) on diseases, such as rheumatoid arthritis,34 HBV,35 and so on. However, most studies failed to show any significant associations, except in cervical cancer; one previous study found that rs187084 (T-1486C) affected susceptibility to cervical cancer in Chinese women 36.…”
Section: Discussionmentioning
confidence: 99%